2022
DOI: 10.13075/ijomeh.1896.01894
|View full text |Cite
|
Sign up to set email alerts
|

Effort-reward imbalance and job strain index associated with health-related quality of life for civil servants in a national survey: the mediation effect of job support and over-commitment

Abstract: Work-related stress (WRS) is significantly associated with health-related quality of life (HRQoL), but the amounts of evidence on differences of effort-reward imbalance (ERI) and job strain index (JSI) remain sparse and have limited generalizability. Therefore, we aimed to assess the association between ERI and JSI with HRQoL and assess the mediation effect of social support (JS) and over-commitment (OC) on this association in Taiwan's civil servants. Material and Methods: A cross-sectional national survey was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…The effort-reward (ER) ratio, with effort as the numerator and reward as the denominator, quantifies the amount of ERI. A higher ER imbalance (ratio > 1.0) tends to be associated with work stress and burnout, work-life imbalance and quality of life [ 24 , 25 ]. Hammig et al [ 24 ] have investigated the relationships between ERI and work-life imbalance, and they found a positive association between ERI and work-life imbalance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The effort-reward (ER) ratio, with effort as the numerator and reward as the denominator, quantifies the amount of ERI. A higher ER imbalance (ratio > 1.0) tends to be associated with work stress and burnout, work-life imbalance and quality of life [ 24 , 25 ]. Hammig et al [ 24 ] have investigated the relationships between ERI and work-life imbalance, and they found a positive association between ERI and work-life imbalance.…”
Section: Introductionmentioning
confidence: 99%
“…Hammig et al [ 24 ] have investigated the relationships between ERI and work-life imbalance, and they found a positive association between ERI and work-life imbalance. Tseng et al [ 25 ] examined the relationships between ERI and quality of life, and found a negative association with physical, mental components. Therefore, we used ERI as the variable of the management system to examine its relationship with QWL.…”
Section: Introductionmentioning
confidence: 99%